Aerobic rice–zero tillage wheat A way forward for enhancing income and resource use efficiency - Shahane, Amit Anil; Shivay, Yashbir Singh (Indian Farming, 2019)
Rice-wheat cropping system occupies the largest area and therefore evaluating different avenues of cultivation methods and nutrient management strategies for potential income and resource are needed. The two years study showed that net returns in aerobic rice system followed by zero-tillage wheat (ARS-ZTW) were increased by 5,700 and 10,100 `/ha overpuddled transplanted rice followed by conventional drill sown wheat (PTR-CDW). The study showed potential of ARS– ZTW among cultivation methods, Zn fertilization, and microbial inoculations in increasing profitability and efficiency in energy, water and nutrient use.